Disparities in Adverse Event Reporting for Hospitalized Children. Issue 6 (7th September 2022) - Halvorson, Elizabeth Eby; Thurtle, Danielle P.; Easter, Ashley; Lovato, James; Stockwell, David
Abstract : Objectives: Hospitals rely on voluntary event reporting (VER) for adverse event (AE) identification, although it captures fewer events than a trigger tool, such as Global Assessment of Pediatric Patient Safety (GAPPS). Medical providers exhibit bias based on patient weight status, race, and English proficiency. We compared the AE rate identified by VER with that identified using the GAPPS between hospitalized children by weight category, race, and English proficiency. Methods: We identified a cohort of patients 2 years to younger than 18 years consecutively discharged from an academic children's hospital between June and October 2018. We collected data on patient weight status from age, sex, height, and weight, race/ethnicity by self-report, and limited English proficiency by record of interpreter use. We reviewed each chart with the GAPPS to identify AEs and reviewed VER entries for each encounter. We calculated an AE rate per 1000 patient-days using each method and compared these using analysis of variance. Results: We reviewed 834 encounters in 680 subjects; 262 (38.5%) had overweight or obesity, 144 (21.2%) identified as Black, and 112 (16.5%) identified as Hispanic; 82 (9.8%) of encounters involved an interpreter. We identified 288 total AEs, 270 (93.8%) by the GAPPS and 18 (6.3%) by VER. A disparity in AE reporting was found for children with limited English proficiency, with fewer AEs by VER ( P = 0.03) compared with no difference in AEs by GAPPS. No disparities were found by weight category or race. Conclusions: Voluntary event reporting may systematically underreport AEs in hospitalized children with limited English proficiency.